2012
DOI: 10.1063/1.4710542
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Doppler spectra of infrared hyperfine transitions of nitric oxide using a pulse modulated quantum cascade laser: Rapid passage, free induction decay, and the ac Stark effect

Abstract: Using a low power, rapid (nsec) pulse-modulated quantum cascade (QC) laser, collective coherent effects in the 5 μm spectrum of nitric oxide have been demonstrated by the observation of sub-Doppler hyperfine splitting and also Autler-Townes splitting of Doppler broadened lines. For nitrous oxide, experiments and model calculations have demonstrated that two main effects occur with pulse-modulated (chirped) quantum cascade lasers: free induction decay signals, and signals induced by rapid passage during the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In the following paper 21 we demonstrate an alternative way of studying the interaction of light from a frequencychirped QC laser with NO by creating a fast scanning probe pulse that modulates the main QC laser output.…”
Section: Discussionmentioning
confidence: 99%
“…In the following paper 21 we demonstrate an alternative way of studying the interaction of light from a frequencychirped QC laser with NO by creating a fast scanning probe pulse that modulates the main QC laser output.…”
Section: Discussionmentioning
confidence: 99%
“…9 In that study 35% population transfer was achieved and RP structure observed within Lambdip spectra. Other coherent phenomena may also be observed with rapidly chirped cw QCLs and particularly striking is the work by Duxbury et al, 10,11 demonstrating the electric field induced Autler-Townes splitting in NO. In this case the splita) E-mail: grant.ritchie@chem.ox.ac.uk ting, observed in a low pressure sample of NO over a pathlength of 100 m, was also found to be chirp rate dependent.…”
Section: Introductionmentioning
confidence: 91%
“…where the complex amplitude of the laser radiation is (8) and field E med (t, z) is related to coherent emission of the medium. Then, we have…”
Section: Oscillation Of Coherent Emission Of An Absorbing Mediummentioning
confidence: 99%
“…A detailed comparison was not conducted in [4] because, on the one hand, the frequency sweeping rates of classical injection lasers were already at the limit, and, on the other hand, the speed of recording fast signals in the IR spectral range was also limited. With the advent of fast frequency swept quantum-cascade lasers and modern means of recording spectra, many researchers returned to investigation of these affects [6][7][8][9][10]. In general, the results obtained…”
Section: Introductionmentioning
confidence: 99%